2015
DOI: 10.2308/isys-51341
|View full text |Cite
|
Sign up to set email alerts
|

Applying Basic Gamification Techniques to IT Compliance Training: Evidence from the Lab and Field

Abstract: Companies depend on internal control to protect the integrity of information systems. IT security and data privacy training are critical controls for safeguarding company information. Employees often dislike the training, however, which can cause a lack of attention to, and poor understanding of, training concepts leading to less effective internal control. To improve the training experience, companies are implementing principles of games in employee training modules, a practice known as gamification. Utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 26 publications
1
55
0
1
Order By: Relevance
“…In contrast to Baxter et al (2015), who only measured gamification impact from a one-time effort, the long-term effects of a durable program would be of much greater interest. From our work we derive a hypothesis that although short-term learning outcomes may be reduced with gamification, there is a potential to keep people open to learning about security at more occasions, than without gamification.…”
Section: Further Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Baxter et al (2015), who only measured gamification impact from a one-time effort, the long-term effects of a durable program would be of much greater interest. From our work we derive a hypothesis that although short-term learning outcomes may be reduced with gamification, there is a potential to keep people open to learning about security at more occasions, than without gamification.…”
Section: Further Workmentioning
confidence: 99%
“…It is however not clear which aspects of gamification were used in the game. Baxter et al (2015) present a study which utilises elements such as a story, goals for the employee, feedback and progress. The authors acknowledge that their solution lacks "other gamification techniques such as competition based on points and leaderboards, achievement badges or levels, or virtual currencies".…”
Section: Introductionmentioning
confidence: 99%
“…Gamification is the application of game components in supporting the different elements of the learning process (Kulpa, 2017). Some of the popular game components that can be used include animation, rewards, challenges and competitions, avatars and progress (Kostromina & Gnedykh, 2016;Domínguez et al, 2013;Kulpa, 2017;Baxter, Holderness & Wood, 2016). Studies have shown that these components have great effects on student's motivations towards the usage of the e -learning environment (Domínguez et al, 2013).…”
Section: Gamification In the Context Of Learning Processmentioning
confidence: 99%
“…It is believed that the use of gamification in education could motivate and engage students [24], improve learning [25], and increase enjoyment [26]. Christy and Fox [27] used leaderboards for female undergraduate students taking a test and has shown that it could have an effect on the students' academic performance.…”
Section: Gamificationmentioning
confidence: 99%